Anteseden Sensitivitas Etika Auditor Pajak - Tony Wijaya; Nerys Lourensius L.T. (Universitas Proklamasi 45 Yogyakarta, 2012)
This research aims to test the influence of modern tax administration to tax auditor ethical sensitivity in DJP (Direktorat Jenderal Pajak) Jakarta Regional Office. Sample in this research is tax auditor in DJP Jakarta Regional Office. Sample selection is performed based on purposive sampling, there are 182 responder which have been fulfilling the conditions needed. Data collecting conducted by disseminating questionare. The analyzed use the multiple regression. Result of research shows that modern tax administration consist of officer ethics code, etics committee and renumeration have influence to tax auditor ethical sensitivity in DJP Jakarta Regional Office. The result shows that the effects of modern tax administration consist of officer ethics code, etics committee and renumeration to ethical sensitivity has R Square of 0,321 or 32,1%.